The Effectiveness of Role Playing Learning in Improving the Numeracy Skills of Primary School Students: A Systematic Literature Review - Andi Dewi Karmila; Wiryanto Wiryanto; Rooselyna Ekawati (Gemilang Maju Publikasi Ilmiah (GMPI), 2026)
Numeracy is a fundamental skill that must be mastered by elementary school students as the basis for developing mathematical competencies at the next level. This study aimed to analyze the effectiveness of role-playing learning in improving the numeracy skills of elementary school students through a systematic literature review of 13 studies published in the 2020-2025 period. The research method uses a systematic literature review approach with content analysis techniques on articles obtained from the Consensus database, Google Scholar, and national and international journal repositories. The inclusion criteria include research that discusses the implementation of role playing in numeracy learning at the elementary school level with experimental, quasi-experimental, or classroom action research designs. The results of the analysis showed that role playing learning consistently improved students' numeracy skills with the percentage of learning completeness increasing from the range of 40-60% to 92-96% after implementation. Role-playing learning has been proven to be effective in improving understanding of decimal number concepts, counting operations, the ability to solve story problems, mathematical representations, and student motivation and participation in learning. The integration of role playing with other approaches such as Problem-Based Learning, Realistic Mathematics Education, and Teaching at the Right Level strengthens the effectiveness of learning. The limitations of the studies identified included limited topic coverage, research design without adequate control groups, and relatively short duration of interventions. This study recommends replicating studies with a stronger experimental design, more diverse material coverage, and longer implementation duration to measure the long-term impact of role-playing learning on elementary school students' numeracy skills.